2019
DOI: 10.1111/aor.13548
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of acute kidney injury after left ventricular assist device implantation: Evaluation of clinical risk scores

Abstract: Acute kidney injury (AKI) is frequent in patients scheduled for implantation of a left ventricular assist device (LVAD) and associated with increased mortality. Although several risk models for the prediction of postoperative renal replacement therapy (RRT) have been developed for cardiothoracic patients, none of these scoring systems have been validated in LVAD patients. A retrospective, single center analysis of all patients undergoing LVAD implantation between September 2013 and July 2016 was performed. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As reported in previous studies from our institution, 15 our anticoagulation regimen included intravenous unfractionated heparin once chest tube drainage was <50 mL/h to maintain an activated partial thromboplastin time of 50‐60 seconds. Acetylsalicylic acid (100‐300 mg/day) was started 48‐72 hours after HVAD pump implant.…”
Section: Methodsmentioning
confidence: 99%
“…As reported in previous studies from our institution, 15 our anticoagulation regimen included intravenous unfractionated heparin once chest tube drainage was <50 mL/h to maintain an activated partial thromboplastin time of 50‐60 seconds. Acetylsalicylic acid (100‐300 mg/day) was started 48‐72 hours after HVAD pump implant.…”
Section: Methodsmentioning
confidence: 99%
“…Acute kidney injury following cardiac surgery is well‐established predictor of increased mortality 26 . Moreover, acute kidney injury following LVAD implantation is a common complication which prolongs the postoperative course and impairs clinical outcomes 27 . However, our results at the multivariable analysis demonstrated that the site of the outflow graft position is independently associated with long term survival, despite the impairment of the renal function.…”
Section: Discussionmentioning
confidence: 60%
“…Our anti-coagulation regimen follows the previously described one by Pilarczyk et al (2019) [ 12 ] and included intravenous unfractionated Heparin once chest tube drainage was <50 mL/h to maintain an activated partial thromboplastin time of 50 to 60 s. Acetylsalicylic acid (100–300 mg/day) was started 48–72 h after LVAD implantation. Once the patient was stable (chest tubes removed and return of GI function), Heparin was replaced by Warfarin.…”
Section: Methodsmentioning
confidence: 99%